Care and the Influence of Student-Adult Stakeholder Interactions on Young Black Men's College Aspirations. (2nd January 2018) - Warren, Chezare A.; Bonilla, Christian
Abstract : Students' college aspirations precede any decision they may make to apply and enroll in college. College aspirations broadly refer to the formal development of specific plans made by a young person to position themselves to enroll in a four-year college or university after high school. Regular, ongoing interaction with college-educated adults is one important approach for transmitting messages that positively influence young people's college aspirations. This article is an examination of young Black men's descriptions of their interactions with adult stakeholders (e.g., administrators, teachers, professional support staff, etc.), and the influence of those interactions on shaping these young men's ambitions to attend college. Data sources for this phenomenological study include one semi-structured in-depth interview with ten college-aged young Black men from a large midwestern city. Findings reveal the significance of care in adult stakeholder-student interactions, and specific messages about college, for sparking these young Black men's aspirations to attend a four-year college or university. The implications of interactions with youth of color that translate culturally responsive versions of care are discussed.